Interaction of varieties and fungicides across seasons and locations for the control of Asian soybean rust (Phakopsora pachyrhizi) in southwestern Ethiopia - Abebe, A.T.; Belachew, K.; Hailemariam, M.; Sileshi, Y.; Ortega Beltran, A. (Elsevier, 2022)
Soybean is emerging as an important legume and oil crop in Ethiopia. However, the crop has been facing serious threats from Asian Soybean Rust (ASR), causing significant damage to the crop and not allowing it to realize its potential. This study aimed to determine the interaction of three varieties with various fungicide treatments across two seasons and two locations to manage ASR. The experiment was laid out in a RCBD in a factorial [three soybean varieties (V) and six fungicides (F)] treatment combination at two locations (L) for two years (Y) with three replications. The analysis of variance across seasons revealed highly significant V × F × Y interactions for grain yield, and F × Y interactions for severity (%) and AUDPC; while efficacy was significant (P = 0.05). The V × Y interaction showed highly significant differences for AUDPC. Across locations, there were highly significant differences for V × F × L for grain yield and V × L for AUDPC. It was only AUDPC that showed significant (P = 0.05) for the V × F interaction. There were two rates (0.75 and 1 l ha−1) of the fungicide Opera Max that provided the best protection against ASR across locations, varieties, and seasons. The yield loss on the unsprayed control treatment ranged between 29 and 65%. The evidence generated from this study clearly demonstrates the importance of identifying the right variety, rates and types of fungicides for the control of ASR for higher production and productivity of soybean in Ethiopia.